ECOLOGICAL CONSEQUENCES OF AGRICULTURAL USE OF THE NATURAL RESOURCES OF EUROPEAN RUSSIA IN UNDERSTANDING THE SOVIET SCIENTISTS OF 1910–1930s - Tsintsadze, N.S. (Tambov University Review. Series: Humanities, 2016)
On the basis of special scientific literature analysis the views of the Soviet natural scientists on the effects of human impact on the natural resources of European Russia and ways to overcome the social and natural crisis are considered. The opinions of scientists-contemporaries, studying the phenomena in later agrarian society were researched. The relationship of the Soviet and pre-revolutionary scientific schools in the field of agronomy, soil science, climatology and so on were traced. Brief focus on the dialectic relationship of the Soviet government and the natural sciences is made. An overview of the some scientists’ opinions on the environmental consequences of the economic use of natural resources in agriculture is presented. The attention is focused on the research proposals, implemented in the practice. A high degree of concern by the scientific community from the negative consequences of irrational economic activities of society is noted. Particular attention is paid to environmental problems, scientists steppe regions, the most emaciated and requiring immediate re-cultivation. However, state attention to the environmental issues raised by the scientists was utilitarian. Many of the scientists’ proposals were realized with large time intervals. In the pre-war period the authorities perceived only offers of scientists concerning intensification of grass cultivation.